Peningkatan Pertumbuhan dan Sintasan Hidup Ikan Bawal (Colossoma macropumum) dengan Penambahan Ragi Roti dalam Pakan - Usy N. Manurung; Numisye I. Mose (Fakultas Pertanian, Universitas Timor, 2018)
The conducted of this study was to investigate the effect of yeast on growth and survival rate of freshwater pomfret fish. This research used complete randomized design with five treatments, each with 3 replications. The treatments was given by treament A (0 gr yeast/ kg feed), B ( 5 gr yeast/ kg feed), C (10 gr yeast/kg feed), D (15 gr yeast/ kg feed), E (20 gr yeast/ kg feed). Frequency of feeding was 2 times a day 5%bb. This research showed that the addition of yeast significally influenced growth and survival rate of pomfret fish. The higest yeast dossage in feed causing highest growth of pomfret fish.